Answer:
C) 4
Step-by-step explanation:
5g-7g+4+2g
5g-7g+2g+4
-2g+2g+4
4
Answer:
-3x-3
Step-by-step explanation:
We want our equation to look like this
y=mx+b
we know that m= -3 so we just need to find b
We can start by plugging in the ordered coordinates into our equation
3=(-3)(-2)+b
Solve for b
3=6+b
b= -3
Which means our final equation is
y= -3x-3
Answer:
Here we have two triangle rectangles, and we want to know the value of y, the shared cathetus between them.
First, we know that one of them has an angle of 60° and the adjacent cathetus to it is a.
The other has an angle of 30° and the adjacent cathetus is b.
In both cases, the opposite cathetus is y.
Now we can recall the relationship:
Tan(a) = (opposite cathetus)/(adjacent cathetus)
Then we can write:
tan(60°) = y/a
tan(30°) = y/b
And we also know that:
a + b = 15
Then we have 3 equations:
tan(60°) = y/a
tan(30°) = y/b
a + b = 15
To solve this, we first need to isolate one variable in one of the equations, i will isolate a in the third equation:
a = 15 - b
Now we can replace it in the first equation to get:
tan(60°) = y/(15 - b)
i will rewrite this one as:
tan(60°)*(15 - b) = y
then our system is:
tan(60°)*(15 - b) = y
tan(30°) = y/b
now we can isolate b in the second equation to get:
b = y/tan(30°)
and then replace it on the other equation to get:
tan(60°)*(15 - y/tan(30°)) = y
Now we can remember that:
tan(60°) = √3
tan(30°) = (√3)/3
Replacing these in our equation we get:
√3*(15 - y/((√3)/3)) = y
we can rewrite this as:
√3*(15 - y*3/√3) = y
then:
(√3)*15 - y*3 = y
(√3)*15 = y + y*3
(√3)*15 = 4*y
(√3)*15/4 = y
then we get:
Answer:
Sarita’s solution is correct. She made an error in her verification. Sarita was supposed to add the 5 and 7 in the first step.
Step-by-step explanation:
Given the following equation:
The steps to solve it are:
5(x-3)+7(x+4)-73
1. Apply the Distributive property:
5x-15+7x+28=73
2. Add the like terms:
12x+13=73
3. Subtract5 13 from both sides of the equation:
12x+13-(13)=73-(13
12x=60
4. Divide both sides of the equation by 12:
12r/12 = 60/12
x = 5
To verify it, let's substitute into the equation:
5(5-3)+7(5+4)=73
Evaluating, we get:
5(2)+7(9)=73
10+63=73
73=73
Based on this, we can determine that Sarita's solution is correct, but she made an error in her verification (Observe that 5-3 is not equal to -2 )